Skenario Pengembangan Sistem Angkutan Umum Khusus Pendidikan di Kota Palangka Raya - Novellia, Angela; Silitonga, Sutan P.; Riani, Desi (Universitas Batanghari Jambi, 2024)
The heavy traffic conditions, especially during peak hours such as school drop-off and pick-up times on R.A. Kartini Street and W.R. Sudirohusodo Street in Palangka Raya City, result in traffic congestion. Therefore, an alternative transportation solution to schools is needed in the form of Special Education Public Transport to reduce the use of private vehicles. This research aims to determine students' interest in using the level of student interest in the alternative transportation to schools by distributing questionnaires to 5 schools in Palangka Raya City, comprising 2 junior high schools and 3 senior high schools. The questionnaire results were then analyzed to obtain the percentage of students choosing Special Education Public Transport as their mode of transportation to school. Based on the analysis results, out of 336 students surveyed, it was found that 17.86% of students are willing to use the Peugeot Boxer School Minibus with a fare of Rp 2,500, 16.07% are willing to use the Isuzu Elf Microbus NRL with a fare of Rp 2,000, and 4.76% are willing to use the Suzuki New Carry Minibus with a fare of Rp 3,500. There is a need for socialization regarding the positive impacts of using Special Education Public Transport, not only to to reduce the use of private vehicles in Palangka Raya City but also as an alternative transportation method to schools.